2014
DOI: 10.3892/or.2014.3340
|View full text |Cite
|
Sign up to set email alerts
|

Far from resolved: Stromal cell-based iTRAQ research of muscle-invasive bladder cancer regarding heterogeneity

Abstract: The aim of the present study was to globally characterize the cancer stroma expression profile of muscle-invasive bladder cancer in different metastatic risk groups and to discuss the decisive role of biological pathway change in cancer heterogeneity. Laser capture microdissection was employed to harvest purified muscle-invasive bladder cancer stromal cells derived from 30 clinical samples deriving from 3 different metastatic risk groups. Isobaric tags for relative and absolute quantitation (iTRAQ) and two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…MIBC tumour sections were first compared to adjacent normal lesions, 89 and, in an independent approach, stromal cells from MIBC were analysed. 90 The authors reported an upregulation of MMP9, exocyst complex component 4 and myosin-10 and suggested these proteins should be further verified as MIBC-specific protein biomarkers. 90 Prognostic or predictive tissue biomarkers Immunohistochemistry has been widely used to characterize tissue protein biomarkers and to identify potential prognostic or predictive value, thus enabling improved assessment of the risk of disease recurrence and/or progression.…”
Section: Discovery and Verificationmentioning
confidence: 97%
See 2 more Smart Citations
“…MIBC tumour sections were first compared to adjacent normal lesions, 89 and, in an independent approach, stromal cells from MIBC were analysed. 90 The authors reported an upregulation of MMP9, exocyst complex component 4 and myosin-10 and suggested these proteins should be further verified as MIBC-specific protein biomarkers. 90 Prognostic or predictive tissue biomarkers Immunohistochemistry has been widely used to characterize tissue protein biomarkers and to identify potential prognostic or predictive value, thus enabling improved assessment of the risk of disease recurrence and/or progression.…”
Section: Discovery and Verificationmentioning
confidence: 97%
“…90 The authors reported an upregulation of MMP9, exocyst complex component 4 and myosin-10 and suggested these proteins should be further verified as MIBC-specific protein biomarkers. 90 Prognostic or predictive tissue biomarkers Immunohistochemistry has been widely used to characterize tissue protein biomarkers and to identify potential prognostic or predictive value, thus enabling improved assessment of the risk of disease recurrence and/or progression. The same principle also applies to prediction of treatment responses to intravesical BCG instillations in patients with NMIBC and treatment responses to radiotherapy and/or adjuvant or neoadjuvant chemo therapy in patients with locally advanced MIBC.…”
Section: Discovery and Verificationmentioning
confidence: 97%
See 1 more Smart Citation
“…[ 23 ] The dynamic interaction between microenvironment and neoplastic cells has been correlated to VM formation. [ 11 , 19 ] The vasculogenic mimicry phenomenon is significant in bladder cancer microenvironment simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many different non-neoplastic cells exist in the tumor microenvironment and interact with tumor cells. Endothelial cells, fibroblasts, and immune cells are the three main cell types which appear in most cancers and are vital components in enhancing the drug resistance of tumors [103,[114][115][116][117][118][119][120]. Endothelial cells are one of the major components of blood vessels and play an important role in tumor angiogenesis [121].…”
Section: Coculturementioning
confidence: 99%